2009
DOI: 10.1186/1477-3155-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles inhibit VEGF-and IL-1β-induced vascular permeability via Src dependent pathway in porcine retinal endothelial cells

Abstract: The aim of this study is to determine the effects of silver nanoparticles (Ag-NP) on vascular endothelial growth factor (VEGF)-and interleukin-1 beta (IL-1β)-induced vascular permeability, and to detect the underlying signaling mechanisms involved in endothelial cells. Porcine retinal endothelial cells (PRECs) were exposed to VEGF, IL-1β and Ag-NP at different combinations and endothelial cell permeability was analyzed by measuring the flux of RITC-dextran across the PRECs monolayer. We found that VEGF and IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 44 publications
5
73
4
Order By: Relevance
“…We showed here that downregulation of ZO-1, an essential scaffold protein for tight junction assembly, follows activation of VEGFR-2 and Src pathway. We also showed that Src inhibition provided an effective protection of ZO-1 network after SLEs, confirming the major role of Src in ZO-1 downregulation, as was reported in models of ischemia and retinopathy (Sheikpranbabu et al, 2009;Takenaga et al, 2009). It is noteworthy that another Src inhibitor (CGP76030), tested on an in vivo model of epilepsy, was shown to reduce the proconvulsive effects of IL-1␤ , strengthening the interest in investigating Src signaling for epilepsy.…”
Section: Discussionsupporting
confidence: 54%
“…We showed here that downregulation of ZO-1, an essential scaffold protein for tight junction assembly, follows activation of VEGFR-2 and Src pathway. We also showed that Src inhibition provided an effective protection of ZO-1 network after SLEs, confirming the major role of Src in ZO-1 downregulation, as was reported in models of ischemia and retinopathy (Sheikpranbabu et al, 2009;Takenaga et al, 2009). It is noteworthy that another Src inhibitor (CGP76030), tested on an in vivo model of epilepsy, was shown to reduce the proconvulsive effects of IL-1␤ , strengthening the interest in investigating Src signaling for epilepsy.…”
Section: Discussionsupporting
confidence: 54%
“…23 Silver nanoparticles inhibit vascular endothelial growth factor (VEGF)-induced angiogenesis in bovine retinal endothelial cells. 24 Similar studies have proven their inhibitory effect on vascular permeability induced by VEGF, interleukin (IL)-1β, 25 and advanced glycation end product 26 in retinal endothelial cells. The potent antiangiogenic and antipermeability effects of AgNPs, along with their ability to halt tumor progression in Pliss lymphosarcoma cells, have prompted the study of the antitumor effect of AgNPs in ascitic tumors.…”
Section: Introductionmentioning
confidence: 91%
“…It could also favor the healing of corneal epithelial wounds. Previous studies demonstrated that low concentrations of silver nanoparticles rescued vascular endothelial growth factor and advanced glycation end-products induced vascular permeability through upregulation of ZO-1 and occludin 80,81 in porcine retinal endothelial cells. Our data are consistent with previous reports demonstrating that tight junction is important for proper cell function, which can be maintained by the treatment of cells with NAM-rGO.…”
Section: Discussionmentioning
confidence: 99%